Influência da aplicação de fósforo na forma orgânica e inorgânica sobre a produção de panicum maximum cv. Mombaça - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The objective of this work was to point out some of the results of the use of litter in pastures, and the accomplishment of an article presenting the productive responses of the mombaça submitted to different proportions of organic and inorganic fertilizer as source of phosphorus. Brazilian cerrado has an enormous potential of production, however some aspects related to fertility need correction. Dairy cattle and dairy cattle depend directly on pasture as the animal feed base, poorly managed systems and degraded pastures limit production. In this way, looking at pastures as crops and using species capable of responding to fertilization ensure greater fertilization efficiency. The mombaça is a grassy one that presents / displays good indexes of accumulation of dry matter with superior response in production when compared with others of the same genre. Organic fertilizers are used to correct fertility and increase production, so it is very important to know the agronomic potential of this input for pasture production, and to evaluate the possibility of total or partial substitution of chemical fertilization, and what would be the advantages for the sustainability of the Over the years.
Keywords: Perfilhos; Matéria seca; Lotação; Tillers; Dry matter; Stocking.; CIENCIAS AGRARIAS